Integration of social capital through technology use for best practices of breastfeeding peer support networking in Malaysia - Suhairom, Nornazira; Saipudin, Nurul Ain; A. Shukor, Nurbiha; Mohd Kosnin, Azlina; Mohamad Ashari, Zakiah; Zalbahar, Nurzalinda (RMP Publications, 2022)
Literature has shown that breastfeeding success depends on breastfeeding support as breastfeeding until six months is a major challenge for most mothers. In breastfeeding research, the early cessation of breastfeeding is described as the biggest challenge. Many mothers have decided to stop breastfeeding because of a lack of support at home, at work, and in the community. The problems for working mothers derive from their work commitment or workplace support. As for stay-at-home mothers, their challenges stem from the pressure of close relatives on conventional myths and erroneous breastfeeding knowledge. New mothers are often given misinformation on breastfeeding. The use of the Internet and social media to obtain lactation information or support for breastfeeding has been widely discussed in the literature at this time. Studying how social capital may be built through the use of technology is imperative. Incorporating social capital into building healthier communities is crucial to help more women choose and continue to breastfeed. Thus, breastfeeding advocacy in Malaysia needs holistic approaches to protection, promotion, and support aspects. Establishing trust-based networks means not only building strong connections but also improving the dependability of those connections between families, communities, and organizations.